2015
DOI: 10.1016/j.jpainsymman.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Number of Outpatients Receiving Spiritual Assessment: A Pain and Palliative Care Service Quality Improvement Project

Abstract: Background Spirituality is a patient need that requires special attention from the Pain and Palliative Care Service (PPCS) team. This QI project aimed to provide spiritual assessment for all new outpatients with serious life-altering illnesses. Measures Percentage of new outpatients receiving spiritual assessment (Faith, Importance/Influence, Community, Address/Action in care [FICA], psychosocial evaluation, chaplain consults) at baseline and post-interventions. Intervention Interventions included encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…Religious/spiritual support interventions would not decrease exposure to nonaffirming religious environments; however, such interventions can be designed to build psychosocial assets that promote resilience and positive youth development, both of which are identified as protective from negative social and health outcomes in adulthood (Furrow, King, & White, 2004; Gavin, Catalano, David-Ferdon, Gloppen, & Markham, 2010; Lerner, Lerner, & Benson, 2011; Romeo & Kelley, 2009; Schmid & Lopez, 2011). Research on religious/spiritual support interventions in health is primarily focused on helping to understand (Gomez-Castillo et al, 2015) and buffer (Balboni et al, 2013; Chochinov & Cann, 2005; Corwin, Wall, & Koopman, 2012) spiritual pain, anguish, and conflict during severe illness or end of life. Even though there is evidence that religious/spiritual support mitigates psychological distress (Maton, 1989; Sulmasy, 2006), no known studies have examined whether religious/spiritual support interventions were protective against negative psychosocial influencing factors (e.g., internalized homophobia and racial/sexual identity incongruence) that are antecedent to HIV risk for Black MSM.…”
Section: Discussionmentioning
confidence: 99%
“…Religious/spiritual support interventions would not decrease exposure to nonaffirming religious environments; however, such interventions can be designed to build psychosocial assets that promote resilience and positive youth development, both of which are identified as protective from negative social and health outcomes in adulthood (Furrow, King, & White, 2004; Gavin, Catalano, David-Ferdon, Gloppen, & Markham, 2010; Lerner, Lerner, & Benson, 2011; Romeo & Kelley, 2009; Schmid & Lopez, 2011). Research on religious/spiritual support interventions in health is primarily focused on helping to understand (Gomez-Castillo et al, 2015) and buffer (Balboni et al, 2013; Chochinov & Cann, 2005; Corwin, Wall, & Koopman, 2012) spiritual pain, anguish, and conflict during severe illness or end of life. Even though there is evidence that religious/spiritual support mitigates psychological distress (Maton, 1989; Sulmasy, 2006), no known studies have examined whether religious/spiritual support interventions were protective against negative psychosocial influencing factors (e.g., internalized homophobia and racial/sexual identity incongruence) that are antecedent to HIV risk for Black MSM.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous studies have shown that spirituality can increase patients' resistance to the mental health crisis after cancer diagnosis and treatment. In addition, lack of spirituality in patients with serious illness may lead to greater emotional anxiety, more severe pain and fatigue, increased burden of illness and lower quality of life [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lack of spirituality in severe patients may lead to more emotional anxiety, severe pain, and fatigue, increased burden of the disease, and decreased quality of life. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Due to a clinical relationship between spirituality and its strong effects on health outcomes, it is essential for all health-care professionals on the palliative care team (doctors, nurses, clergies, therapists, and social workers) to be well educated about the spiritual concerns of patients. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%